Phantom Train as Integral Image in Vladimir Nabokov’s Mary (1926) - Ziwei Zhu (СибСкрипт, 2024)
In Vladimir Nabokov’s novel Mary (1926), the train is an integral image. It is a metaphor, a symbol, and a leitmotif that generates or attracts many other images. The methods of motif and hermeneutic-interpretative analyses revealed that the train is a phantom that extends onto the characters and the entire artistic reality. The phantom train manifests itself in the interior of the houses where Russian emigrants live, in the city where the fate brought them to, in their own appearances, names, words, and actions. The phantom personages are shadows in a postmortem existence while Berlin is wrapped in smoke, clouds, and vapor. In this duality, Russia is as ghostly as Berlin in the main character’s memories. Initially, Russia and Mary are light and weightless, but the gloomy phantom train gradually penetrates into these memories. The end of the novel is ambiguous. Probably, it correlates with Nikolai Gumilev’s poem The Lost Tram. Besides, Nabokov liked to clash mutually exclusive plot developments. Apparently, the main character both leaves the phantom reality and stays in it as he boards the train that takes him away from Berlin and his past love.